Introducing Self-Regulated Performance Evaluation Model (SRPEM) for a comprehensive and effective evaluation of academic performance - Noor Liza Adnan; Rokiah Muda; Wan Noor Hazlina Wan Jusoh; Rohana Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2024)
Academics responsibilities have multiplied in recent years as exhibited in yearly Key Performance Indicators (KPIs) outlined by higher educational institutions’ performance evaluation system. Performance evaluation at universities is claimed to cause unnecessary stress due to various factors. The criteria and metrics set in the evaluation do not accurately capture the complexities of academic responsibilities, leading to pressure and anxiety as academics try to meet the targets that may not align with their styles and interests. Therefore, this study aims to propose the Self Regulated Performance Evaluation Model (SRPEM), designed to assess employees' performance fairly without causing undue stress, particularly for academics in HEIs. This qualitative research involved face-to-face semi structured interviews conducted online via the Google Meet application with 16 academicsselected based on purposive sampling from different institutions who are involved directly with the evaluation process, a state Deputy Mufti, a Registrar and Deputy Registrar. The interviews gathered insights on the current performance evaluation systems, suggestions for improvement, and opinions on fair evaluation practices. Based on the collected input, the SRPEM was developed, consisting of three key components: the performance evaluation process, the evaluators, and the measures. Unlike previous studies that heavily rely on quantitative measures, this model takes into account humanistic and spiritual aspects by integrating theories such as self-determination theory. The SRPEM aims to create a comprehensive and effective performance evaluation system that aligns with the needs and values of academics. Although the proposed model may seem idealistic, it was created by modifying the current evaluation system based on input from interviewees and suggestions from theories. As such, it is advisable to do an experimental investigation in future research to confirm its significance.